Rehabilitacijska obravnava v času pandemije COVID-19 v Thermani Laško - Kadoič Krašovec, Maruša (Rehabilitacija (Ljubljana), 2021)
Slovenia is facing a rapid spread of infections with the consequent growth of the number of patients with COVID-19 (Coronavirus disease 2019) since march 2020. The first lockdown was sudden, with limited access to health care and rehabilitation. In Thermana Laško we continued to provide rehabilitation to post-acute patients discharged from hospitals in order to improve functional outcome and quality of life. Initially, there were no specific guidelines for safe rehabilitation and work in rehabilitation centres, so we created our own safety protocols and constantly upgraded them based on new recommendations to offer safe rehabilitation treatment to even the most vulnerable patients. Despite transient declines in coronavirus cases and increased access to health and medical services, the pandemic is not under control. The second coronavirus wave is much worse than the first, as many patients have a more severe course of COVID-19. Due to long-term hospital care and complications of illness after discharge from acute hospitals, the number of patients who need intensive rehabilitation treatment is also increasing. Considering the safety protocols and guidelines, we also carry out successful rehabilitation of patients after recovering from COVID-19 in our institution.
Keywords: COVID-19; pandemic; pandemija; rehabilitacija; Rehabilitation; spa; zdraviliško zdravljenje